Implementation of Eating Ethics in the Perspective of Prophetic Hadith: A Study of Living Sunnah on Consumers of UIN Alauddin Makassar Canteen - Mustika Rahayumustika (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2023)
This paper discusses the implementation of eating ethics from the perspective of the Prophet’s hadith. (a study of living sunnah on UIN Alauddin Makassar canteen consumers). The purpose of this paper is to identify hadiths on eating ethics and the quality of hadiths on eating ethics from the perspective of the Prophet SAW’s hadith, as well as to find out the implementation of eating ethics hadiths for canteen consumers at UIN Alauddin Makassar. This paper uses a qualitative research method in the form of a library-field. The results of the study show that: 1) Identification of hadiths uses two takhrij methods and there are 11 identified hadiths, 2) The quality of the hadiths regarding eating ethics as a whole is acceptable because of the 11 hadiths there is 1 quality hadith hasan based on the quality of the nurse and other sauthentic, 3) the implementation of hadith understanding about eating ethics in UIN Alauddin Makassar canteen consumers is reading bismillah(prayer) and using the right hand are two things that are never left out when eating. Blowing food some of the consumers blow some not. Likewise with eating and drinking while standing, 8.7% did not do it, 91.2% did. Overeating, some do and some don’t. Then, the things that are never done are eating three fingers, criticizing food, taking food far away, leaving food at the call to prayer, eating together with one large tray. There is one thing that cannot be separated chat (talk) while eating.